Assessment of customer satisfaction with logistics service in the light of the results of the research = Ocena zadowolenia klienta z obsługi logistycznej w świetle wyników badań - Kułyk, Piotr; Michałowska, Mariola; Kotylak, Sławomir (Zielona Góra: Faculty of Economics and Management Press)
In an era of rapidly growing competition logistic customer service is growing increasingly important and is becoming a substantial factor in the success of companies operating in the market. Therefore, it is necessary to improve the components affecting the quality of customer service. Taking appropriate action in this regard, and thus preparing and implementing an appropriate logistic customer service strategy becomes important from the point of view of both the survival and development of enterprises, and to achieve sustainable competitive advantage.
Keywords: elementy logistyczne; korzyści usługi; koszty obsługi; strategia obsługi klienta; customer service; logistic elements; benefits of service; costs of service; customer service strategies